Central retinal artery occlusion and central retinal vein occlusion in contralateral eye - de Medeiros, Felipe Beltrão [UNESP]; Costa, Isabela Porto Silva; de Araujo, João Pedro Vedovelli; de Souza, Jaqueline Cordeiro; de Medeiros, Hilton Arcoverde Gonçalves (Revista Brasileira de Oftalmologia, 2021)
The case of a 55-year-old male who presented central retinal vein occlusion with marked macular ischemia in left eye is reported. Despite the intervention with sustained-release dexamethasone polymer injection and other clinical measures, the visual acuity was severely reduced in left eye. After 8 months, he returned to the emergency with acute visual loss of 2 hours of progression in right eye due to a central retinal artery occlusion, sparing only the territory of the cilioretinal artery. Patient underwent clinical maneuvers with anterior chamber paracentesis and intravenous injection of tissue plasminogen activator. Fluorescein angiography immediately after the procedures showed recanalization, but despite arterial vasodilation, no complete recanalization was observed after 24 hours. The patient developed retinal atrophy.
Oclusão da artéria central da retina com oclusão da veia central em olho contralateral
Keywords: Ischemia; Retinal artery; Retinal diseases; Retinal vein